Undiagnosed Cervical Ectopic Pregnancy is a Threat to Life - Shama Chaudhry; Misbah Hareem; Rubina Hussain (ziauddin University, 2024)
Cervical ectopic pregnancy implants in the lining of endocervical canal. Cervical ectopic is rare form of ectopic pregnancy and incidence of cervical ectopic pregnancy is 1:9000 pregnancies .We are reporting a case report of a 35 years old female P1+0 was presented in OPD with continuous per vaginal bleeding since 3 months. MRI pelvis showed 4.8×4.5×4.2 cm lesion involving the entire cervix including stroma with partial obstruction of endocervical canal. Growth was removed digitally with difficulty and was sent for frozen section & biopsy. Hemostasis was secured with great difficulty by taking sutures & cervix was packed. Report of frozen section showed products of conception. Injection Methotrexate was given intramuscularly. Cervical ectopic pregnancy was associated with significant hemorrhage which led to hysterectomy in the past. Mortality is limited and fertility is preserved by improved ultrasound resolution, MRI and earlier detection of these pregnancies which has led to the development of more conservative treatments. KEY WORDS: Cervical ectopic pregnancy, Methotrexate, endocervical canal, frozen section